2012
DOI: 10.1111/1475-6773.12000
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Primary Care Practices Engage in Practice Improvement Efforts Whereas Others Do Not?

Abstract: Objective.To understand what motivates primary care practices to engage in practice improvement, identify external and internal facilitators and barriers, and refine a conceptual framework. Data Sources. In-depth interviews and structured telephone surveys with clinicians and practice staff (n = 51), observations, and document reviews. Study Design. Comparative case study of primary care practices (n = 8) to examine aspects of the practice and environment that influence engagement in improvement activities. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…In addition, the results of the ACIC survey of PCPs and practice staff at baseline found that the site not moving forward with implementation was with the fewest resources in place to deliver chronic illness care. These findings confirm those who have recently identified the importance of incentives, resources, and priorities as necessary elements in the process of engaging practices in improvement efforts [37] and that assessing and supporting infrastructure may be an important, but often overlooked, first step toward implementing and sustaining new interventions.…”
Section: Maintenancesupporting
confidence: 86%
“…In addition, the results of the ACIC survey of PCPs and practice staff at baseline found that the site not moving forward with implementation was with the fewest resources in place to deliver chronic illness care. These findings confirm those who have recently identified the importance of incentives, resources, and priorities as necessary elements in the process of engaging practices in improvement efforts [37] and that assessing and supporting infrastructure may be an important, but often overlooked, first step toward implementing and sustaining new interventions.…”
Section: Maintenancesupporting
confidence: 86%
“…These findings are consistent with a previous study that found that knowledge and expertise, technical assistance, and finances are critical resources that can enable transformation in small primary care practices. 17 Most providers had limited awareness of the Searchlight data portal, which was difficult to use for the small number of individuals who were familiar with this program element. These findings suggest an opportunity to improve the user-friendliness of the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the desire to do so is there, many will need strong signals that this change will be rewarded by payers and patients. 69 A recent study of innovative practices teaches us that much of the joy of practice is sapped when primary care physicians are doing tasks that keep them from doing what they are best trained to do. 60 Family medicine becomes most effective, perhaps most enjoyable, when team members in the practice are working collaboratively at the top of their capabilities and training.…”
Section: Discussionmentioning
confidence: 99%